Pregnancy Outcome of Twin Pregnancy at Gandaki Medical College Teaching Hospital, Pokhara, Nepal - Tripathi, M; Shrestha, R (Journal of Gandaki Medical College-Nepal, 2018)
Objectives: To evaluate maternal and neonatal complications and pregnancy outcomes of twin pregnancies. Methods: The cross sectional study was conducted using retrospective data on the twin pregnancies with more than 28 weeks of gestational age. The study used data over a period of five years, from March 10, 2010 to March 9, 2015 in the Department of Obstetrics and Gynecology, GMC Teaching Hospital Pokhara. Results: Of the 50 twin pregnancies, the most common maternal complication was preterm delivery (40%). Other maternal complications were anemia (36%), pregnancy induced hypertension (14%), premature rupture of membranes (14%), postpartum hemorrhage (12%) and antepartum hemorrhage (6%). Median gestational age at delivery was 37 weeks. Most common route of delivery was cesarean section (66%). Most common neonatal complication was low birth weight (48%) births first twin and second twin 56%. Conclusion: Twin pregnancy has high maternal and neonatal complications, especially preterm delivery that increases the risk of significant neonatal morbidity and mortality.